A multicriteria model for the selection of the transport service provider: A single valued neutrosophic DEMATEL multicriteria model - Liu, Feng; Aiwu, Guan; Lukovac, Vesko; Vukic, Milena (Decision Making: Applications in Management and Engineering, 2018)
The decision-making process requires, a priori, defining and considering certain factors, especially when it comes to complex areas such as transport management in companies. One of the most important items in the initial phase of the transport process that significantly influences its further flow is decision-making about the choice of the most favorable transport provider. In this paper a model for evaluating and selecting a transport service provider based on a single valued neutrosophic number (SVNN) is presented. The neutrosophic set concept represents a general platform that extends the concepts of classical sets, fuzzy sets, intuitionistic fuzzy sets, and an interval valued intuitionistic fuzzy sets. The application of the SVNN concept made a modification of the DEMATEL method (Decision-making Trial and Evaluation Laboratory Method) and proposed a model for ranking alternative solutions. The SVNN-DEMATEL model defines the mutual effects of the provider’s evaluation criteria, while, in the second phase of the model, alternative providers are evaluated and ranked. The SVNN-DEMATEL model was tested on a hypothetical example of evaluation of five providers of transport services.